Respostas

A melhor resposta!
  • Usuário do Brainly
2014-07-25T15:16:26-03:00
A)
(2x+3y)²+3(x-y)(-2x+4y)

4x²+12xy+9y²+3(-2x²+4xy+2xy-4y²)

4x²+12xy+9y²-6x²+12xy+6xy-12y²=
4x²-6x²+12xy+12xy+6xy+9y²-12y²=
-2x²+30xy-3y²

b)
(3x²-4z)²-[2x+3(x+2)(x-4)]-(x²-3z)²

9 x^{4} -24 x^{2} z+16 z^{2} -[2x+3( x^{2} -2x-8)]-( x^{4} -6 x^{2} z+9 z^{2} )=

9 x^{4} -24 x^{2} z+16 z^{2} -[2x+3 x^{2} -6x-24]- x^{4} +6 x^{2} z-9 z^{2} =

9 x^{4} -24 x^{2} z+16 z^{2} -2x-3 x^{2} +6x+24- x^{4} +6 x^{2} z-9 z^{2} =

9 x^{4} - x^{4} -24 x^{2} z+6 x^{2} z+16 z^{2} -9 z^{2} +3 x^{2} -2x+6x+24=

8 x^{4} -18 x^{2} z+7 z^{2} +3 x^{2} +4x+24
1 5 1